Direct and transcallosal contribution to the cortical visual evoked response in rats. - Silveira, L; Heywood, C; Cowey, A (1989)
The averaged visually evoked cortical potential (VECP) in response to contrast reversal of a grating was measured on striate cortex over a range of spatial frequencies and contrasts. The response to binocular or monocular stimulation was almost abolished by unilateral section of the optic tract on the side of the recording, indicating that the transcallosal pathway makes little contribution to the VECP. Additional section of the corpus callosum, and application of spreading depression to the normal hemisphere shows that the small response following tract section was transcallosal. It was confined to stimuli of low spatial frequencies and high contrast.